PERILAKU DAN JENIS PAKAN ORANGUTAN KALIMANTAN (PONGO PYGMAEUS LINNAEUS, 1760) DL KALIMANTAN - PURWO KUNCORO; SUDARYANTO -; LUH Puru ESWARYANTI KUSUMA YUNI (Program Studi Biologi, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Udayana, 2008)
Data collection was conducted using focal animal instantaneous. The daily activity data were group based on their ethogram and was adopting